A Modified Alcohol SBI for Use among Older Adults Living with HIV. (December 2020) - Nguyen, Annie L.; Lake, Jordan E.; Preciado, Diane; Liao, Diana; Moore, Alison A.; del Pino, Homero E.
Older adults living with HIV may have health conditions that amplify the potentially negative health effects of alcohol use. We adapted the Comorbidity Alcohol Risk Evaluation Tool (CARET) screening tool for at-risk drinking to reflect HIV/AIDS and related conditions, medications, and behaviors. The adapted CARET-HIV along with a brief intervention was administered to 27 older men living with HIV. The CARET-HIV identified the same number of at-risk drinkers as the original CARET (n = 24) but identified more risk domains. Most participants welcomed receiving information about risks associated with their drinking, but some felt "embarrassed" or "guilty" discussing their drinking. This is particularly salient within the context of HIV discourse, which has historically assigned blame of HIV infection on personal choices. The SBI was generally acceptable to participants. The modified CARET can help providers integrate discussion of alcohol use into the context of HIV care for personalized feedback.